Determination of Similarity and Variance in Energy and Depositional Environment, the Difference in Diagenesis and the Variance in the Petrophysical Properties of Reservoir Rocks in Zubair Formation , South Iraq (Baghdad Science Journal, 2009)
Records of two regionalized variables were processed for each of porosity and permeability of reservoir rocks in Zubair Formation (Zb-109) south Iraq as an indication of the most important reservoir property which is the homogeneity , considering their important results in criterion most needed for primary and enhanced oil reservoir .Z and F tests that were calculated for the two above mentioned properties of pair units of Zubair Formation have shown the difference in depositional energy and different diagenesis between units IL and AB , DJ and AB , and the similarity in grains size , sorting degree , depositional environment and pressure gradients between IL and AB units , LS and IL units ; also the difference in the properties above between AB and DJ units , AB and MS units .The coefficient of variation results have shown that AB and MS units have high values indicating heterogenous normal distribution and low values of porosity and permeability compared with other Zubair Formation units .